Ab initio calculations on uracil-water - van Mourik, T; Price, S; Clary, D (1999)
The potential energy surface for the interaction of uracil with one water molecule is investigated using ab initio techniques. The structures of four cyclic minima, as well as two transition-state structures, have been determined using second-order Møller-Plesset perturbation theory' (MP2) and the interaction-optimized DZPi basis set. At the optimized geometries, the counterpoise-corrected interaction energies have also been computed with a slightly larger basis set containing bond functions, labeled ESPB. The MP2/ESPB calculations predict De for the four uracil-water minima to be -40.0, -31.8, -33.5, and -26.6 kJ/mol. The barrier height between the global minimum and the adjoining local minimum (with De = -31.8 kJ/mol) is found to be as much as 23 kJ/mol, while the barrier height between the two most stable local minima (De = -33.5 and -31.8 kJ/ mol) is only 10 kJ/mol. For the global minimum we also investigated the effect of basis set superposition error (BSSE) on the two hydrogen bond distances, as well as the effect of freezing the monomer geometries during optimization. It is found that BSSE decreases the hydrogen bond lengths by about 0.1 Å, while freezing the intramolecular geometries reduces the uracil-water interaction energy by less than 2 kJ/mol.